Gender justice and food security in India: A review - Rao, Nitya; Pradhan, Mamata; Roy, Devesh (International Food Policy Research Institute, 2017)
There is ample evidence to suggest a strong correlation between gender inequality and food and nutrition insecurity, yet the policy discourse around food and nutrition security in India has largely been gender-blind. This paper, based on a review of existing literature and emerging research, emphasizes the need to place gender justice at the center of all food and nutrition interventions, if food and nutrition security for all is to be achieved. Rather than exclusively targeting women and often overburdening them with the responsibility for household food security, policy approaches need to encourage and enhance reciprocity and sharing between men and women in households and communities, and empower them to negotiate effectively vis-à-vis institutions of the state, markets, and society. With the aim of moving toward gender-transformative approaches in policies and programs for achieving food and nutrition security in India, in this paper we set out an alternate framing of the agenda, drawing on what the evidence tells us. We flag emerging issues that need to be addressed to draw out possible implications for research and policy in gender-just food and nutrition interventions in India.